Temporal grouping and direction of serial recall. - Liu, Yang S.; Caplan, Jeremy B. (Memory & Cognition, 2020)
When lists are presented with temporal pauses between groups of items, participants' response times reiterate those pauses. Accuracy is also increased, especially at particular serial positions. By comparing forward with backward serial recall, we tested whether the influence of temporal grouping is primarily a function of serial position or output position. Results favored the latter, both when recall direction was known to participants prior to (Experiment 2) or only after (Experiment 2) studying each list. Alongside fits of variants of a temporal distinctiveness-based model, our findings suggest that the influence of temporal grouping is not just a consequence of grouping information stored during the study phase. Rather, it critically depends on participants cueing with within-chunk position during recall, combined with response suppression.